Effects of workload level on muscle recruitment in cycling - Priego, J. I.; Bini, R. R.; Lanferdini, F. J.; Carpes, F. P. (Human Movement, 2014)
Despite the volume of studies addressing muscle activation during pedaling, it is unclear whether changes in workload level during cycling could dictate motor unit recruitment. The present study investigated the frequency content of lower limb muscle activation during submaximal workloads. Methods. Twelve male competitive cyclists pedaled at three workload levels: (1) maximum aerobic power output (POMAX), (2) first ventilatory threshold (POVT1), and (3) second ventilatory threshold (POVT2). Muscle activation was recorded from the right vastus medialis (VM), rectus femoris (RF), long head of biceps femoris (BF), tibialis anterior (TA), gastrocnemius medialis (GM), and soleus (SOL) muscles. Data from muscle activation were assessed using frequency band analysis. High and low frequencies and overall muscle activation were normalized to that collected at POMAX. Results. Greater overall activation was observed for VM (27%, p < 0.01, d = 1.22), RF (24%, p < 0.01, d = 0.96), BF (33%, p < 0.01, d = 1.43), GM (10%, p < 0.05, d = 0.91), and SOL (16%, p < 0.05, d = 0.81) at POVT2 than POVT1. No differences were observed in the high or low frequencies relative to overall muscle activation. Conclusions. Cyclists sustain changes at submaximal workloads via an equally distributed increase in muscle activation with no potential changes in motor unit recruitment.